Ecological Study of Winter Weeds in Tea [Camellia Sinensis (L.) Kuntze] Plantations of Dibrugarh and Tinsukia Districts of Assam - Gogoi, S. N.; Sarma, S. K. (Indian Forester, 2009)
Ecological investigation covering phyto-sociological attributes of 123 winter weed species have been reported in the article from the tea fields of Dibrugarh and Tinsukia districts of Assam. Importance Value Index (IVI) of each species was calculated. Among the weed species, Axonopus compressus (38.986), Imperata cylindrica (26.353), Ageratum conyzoides (26.251), Cynodon dactylon (14.383), Oxalis corniculata (11.348) and Gnaphalium indicum (10.39), are identified as the most dominant species in the tea fields. The study showed variation in their IVI values in different study sites due to for change in the physicochemical properties of soil of the study sites. Although the physical properties of soils are almost similar in all the study sites, their nutrient contents show variations, which may be the prime cause of variation in the IVI values.